2022
DOI: 10.3390/genes13091678
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny, DNA Barcoding, and ITS2 Secondary Structure Predictions in the Medicinally Important Eryngium Genotypes of East Coast Region of India

Abstract: Commercial interest in the culinary herb, Eryngium foetidum L., has increased worldwide due to its typical pungency, similar to coriander or cilantro, with immense pharmaceutical components. The molecular delimitation and taxonomic classification of this lesser-known medicinal plant are restricted to conventional phenotyping and DNA-based marker evaluation, which hinders accurate identification, genetic conservation, and safe utilization. This study focused on species discrimination using DNA sequencing with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The alignment of the primary nucleic acid sequences could be optimized and modified using the secondary ITS2 information, contributing to the accuracy and robustness of the phylogeny [ 45 ]. Previous research had shown that genetic structure uniqueness at the conserved nuclear region could be useful for developing species-specific primers, as reported in a previous study [ 18 ]. Meanwhile, little information was available on the function and secondary structure of ITS1, leaving a gap in the knowledge on whether ITS1 secondary structure prediction could enhance species identification.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The alignment of the primary nucleic acid sequences could be optimized and modified using the secondary ITS2 information, contributing to the accuracy and robustness of the phylogeny [ 45 ]. Previous research had shown that genetic structure uniqueness at the conserved nuclear region could be useful for developing species-specific primers, as reported in a previous study [ 18 ]. Meanwhile, little information was available on the function and secondary structure of ITS1, leaving a gap in the knowledge on whether ITS1 secondary structure prediction could enhance species identification.…”
Section: Discussionmentioning
confidence: 88%
“…According to the previous literature, trn L and ITS DNA barcodes can be used to distinguish between the Nepenthes species based on their geographical origin area [ 17 ]. Meanwhile, other studies concluded that RNA secondary structure prediction is an advanced tool for species discrimination [ 18 ], and the integration of secondary structure information in species identification can significantly improve its accuracy for other plant species [ 18 , 19 , 20 ]. However, there are not many reports on how ITS1 and ITS2 secondary structure predictions can be used together to differentiate between species.…”
Section: Introductionmentioning
confidence: 99%
“…Since every plant has a different DNA sequence, it includes using a short, standardized DNA sequence as a “barcode” to identify a certain species of plant. The chloroplast gene rbcL, matK, and trnH-psbA are the most frequently used barcode region, but the ITS (Internal Transcribed Spacer) marker has been also used in recent studies. , In a study, the ITS marker was used for DNA barcoding of Euphorbiaspecies, and the researchers found that this marker was able to effectively distinguish between Euphorbia subgenus and closely related species. It was reported that the ITS marker might be used to identify Euphorbia species and to verify the authenticity of the plant material used in conventional medicine and the pharmaceutical industry .…”
Section: Introductionmentioning
confidence: 99%
“…DNA barcoding -is a standard gene fragment1 for identification of species. It has been developing rapidly in recent yearsbecome a useful tool for biodiversity investigation and monitoring, and molecular phylogeny and evolution [16]. Both primers (matk+rbcl) -conserved DNA sequences-are used as barcode primers, and would be an accurate method for identification and differentiation of species [17].…”
Section: Introductionmentioning
confidence: 99%